HEMATOLOGICAL CHANGES IN PRISONERS WITH HIGHER BLOOD LEAD LEVELS COMPARED WITH GENERAL POPULATION - Al Khatib, Ahed J; Taani, Haitham M; Al Asseiri, Mohammed; Qasem, A’aesha M; Kassab, Manal; Laiche, Fatima (European Scientific Journal, ESJ, 2013)
Lead (Pb) is one of the major environmental health hazards. From a biological point of view, lead is considered as anon-essential trace element and has no any biological function. The aims of the present study were to study blood lead levels among prisoners in the Northern of Jordan. Two prisons in the northern of Jordan were visited. Blood samples were collected and evaluated for hematological parameters and blood lead level. The study included 73 participants (46 prisoners and 27 participants as control). Study findings revealed low exposure of lead among study participants. The mean blood lead level among prisoners was 0.924 Î¼g/dl, and 0.57Î¼g/dl among control group. Hematological parameters under study were less in prisoners compared control group. Study findings revealed significant relationships between blood lead level and hematological parameters among prisoners. Taken together, the present study evaluated the effects of lead exposure on prisoners through studying these effects on some hematological parameters. The findings of the present study indicated that even prisoners had more blood lead levels compared with control group; the exposure variations were not statistically significant, but able to induce changes on studied hematological parameters.